Development of Koperwuz Media Incorporating the Nature of Science (NOS) to Improve Learning Outcomes of Fourth Grade Elementary School Students - Azizah, Laily Nur; Wenda, Dhian Dwi Nur; Kurnia, Ita (Lembaga KITA, 2025)
Low student achievement and limited engagement in science classes, particularly on the topic of changes in the state of matter, prompted this study. Teachers have continued to rely on conventional instructional methods, with teaching materials primarily sourced from textbooks. Existing media have not succeeded in improving learning outcomes, and instructional processes rarely connect scientific concepts to students’ everyday experiences. This research aims to evaluate the validity, practicality, and effectiveness of the Koperwuz instructional comic, which incorporates the Nature of Science (NoS) approach, in enhancing student performance on the topic of phase changes in fourth-grade classes at SDN Tarokan 4 Kediri. The study adopted a Research and Development (R&D) methodology, following the ADDIE development framework. Validation was conducted by subject matter and media experts. Practicality was assessed through large-scale questionnaires completed by both teachers and students, while effectiveness was measured using pretest and posttest scores from a broad trial group. The findings indicate that the Koperwuz comic achieved high validation scores from both media (88%) and subject experts (100%), categorizing it as highly valid. Teacher responses yielded a practicality score of 87%, while students rated it at 75%, suggesting the medium is practical for classroom use. Analysis of learning outcomes showed a significant improvement, with average pretest and posttest scores rising from 60.8 to 90.1. The calculated N-Gain score was 0.7639, classified as high, and the N-Gain percentage reached 76.39%, indicating the medium’s effectiveness. These results support the conclusion that the NoS-based Koperwuz comic is a viable tool for improving science learning outcomes among fourth-grade students.